Mixing apples with oranges? Partisanship and active labour market policies in Europe - Vlandas, T (SAGE Publications, 2013)
There are competing theoretical expectations and conflicting empirical results concerning the impact of partisanship on spending on active labour market policies (ALMPs). This paper argues that one should distinguish between different ALMPs. Employment incentives and rehabilitation programmes incentivize the unemployed to accept jobs. Direct job creation reduces the supply of labour by creating non-commercial jobs. Training schemes raise the human capital of the unemployed. Using regression analysis this paper shows that the positions of political parties towards these three types of ALMPs are different. Party preferences also depend on the welfare regime in which parties are located. In Scandinavia, left-wing parties support neither employment incentives nor direct job creation schemes. In continental and Liberal welfare regimes, left-wing parties oppose employment incentives and rehabilitation programmes to a lesser extent and they support direct job creation. There is no impact of partisanship on training. These results reconcile the previously contradictory findings concerning the impact of the Left on ALMPs.